Evaluation of assays for quantification of DNA in canine plasma as an indirect marker of NETosis. (3rd April 2017) - Smith, Stephanie A.; Lawson, Corinne M.; McMichael, Maureen A.; Jung, Katrina; O'Brien, Mauria; Achiel, Ron
Abstract : Background: Neutrophil extracellular traps (NET), consisting of a filamentous DNA/chromatin‐histone scaffold originating from neutrophils are part of the innate immune response, may be released under a variety of inflammatory conditions and are associated with an increased risk for thrombosis. Objectives: The purpose of this study was to evaluate a SYTOX green fluorescence assay and a histone–DNA complex (hisDNA) ELISA for quantification of NET‐related DNA in canine plasma. Methods: The influence of variations in blood sample handling on assay results was tested. Accuracy of the SYTOX green fluorescence and the hisDNA ELISA was evaluated with dilutional linearity using serial dilutions. Interference was assessed by addition of purified bilirubin or hemoglobin. Precision was determined by calculating the intra‐ and inter‐assay CV. Results: Preanalytic sample handling did not influence DNA measurements by either assay. Citrate and EDTA plasma samples were equivalent. For the DNA fluorescence assay, dilutional linearity was poor due to autofluorescence, which was corrected by addition of canine plasma to the diluent. The presence of bilirubin and hemoglobin also increased autofluorescence, and resulted in falsely low concentrations of DNA. On the hisDNA ELISA, pigmentemia had no effect. Conclusions: Both assays as modified in this study are suitable for measuring DNA in canine EDTA or citrate plasma. However, performance of the fluorescence assay was impacted by pigmentemia, and it was less sensitive than the ELISA in detecting the presence of nucleosome material in the plasma.